Lecture 07. Acids and Bases. Pt. 4. - Ramesh D. Arasasingham (University of California Irvine (UCI), 2013)
(en)UCI Chem 1C General Chemistry (Spring 2013) Lec 07. General Chemistry -- Acids and Bases -- Part 4 Instructor: Ramesh D. Arasasingham, Ph.D. Description: UCI Chem 1C is the third and final quarter of General Chemistry series and covers the following topics: equilibria, aqueous acid-base equilibria, solubility equilibria, oxidation reduction reactions, electrochemistry; kinetics; special topics. Index of Topics: 0:00:00 Review of Carbonic Acid Example 0:15:43 Hydrolysis 0:18:10 Acid Base Properties of Salt 0:39:00 Calculating pH of Salt 0:47:09 Arranging Compounds from Most Acidic to Most Basic